(3EOGQI GdCYeGd GdOhdjI (B/s - (3YGeQ, SGeM YHO GdeWdHs ((3YeGf(B: s (3OGQ GdacQ(B, s, 2010)
(3fXQI YGeI Mhd GOGQI GdGYeGd GdOhdjI , HjFI GOGQI GdYGeGd GdOhdjI , GdJNWjW GdGSJQGJjLj aj TQcGJ GdGYeGd GdOhdjI , JfXje GdGYeGd GdOhdjI h GdQbGHI Ydi GOGQI GdGYeGd GdOhdjI , dBKGQ GdGSJKeGQGJ GdCLfHjI h GSJQGJjLjI GdJehjd aj GdGYeGd GdOhdjI , GSJQGJjLjI GOGQI GdehGQO GdHTQjI Ydi GdeSJhi GdYGdej , GSJQGJjLjI GdJShjb GdOhdj , GdGSJKeGQGJ GdGLfHjI h GNjQG efGN GdGSJKeGQGJ aj GdOhd GdfGejI h HYV ef Ohd GdTQb GdGhSWs
Keywords: (3EOGQI GdCYeGds; (3GdESJKeGQGJ GdCLfHjIs; (3GdJShjbs